Choosing the most appropriate bedding material for broiler production using multicriterial analysis - Garcia, R. G.; Almeida Paz, I. C.L.; Caldara, F. R.; Nääs, I. A.; Pereira, D. F. [UNESP]; Graciano, J. D.; Bernardi, R.; Freitas, L. W.; Schwingel, A. W. (My University, 2011)
This study aimed to select the most appropriate bedding material for use in broiler production and it was based on data from a research which studied the effect of bedding materials in broiler carcass quality, using six distinct types of bedding material. The analytical hierarchy process was applied by adopting selected criteria in accordance to the most important characteristics required by broiler producers. Weights were given to the criteria and a pair wise comparison was done. Results showed that wood shaving was the best alternative (28.3%), followed by rice husk (24.3%) and by chopped Napier grass (Pennisetum pupureum) (13.3%).
Keywords: Alternative bedding material; Analytic hierarchy process; Multicriterial analysis